2016
DOI: 10.1080/02656736.2016.1237681
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation combined with percutaneous ethanol injection for hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: The combination of RFA and PEI appears to be the optimal treatment strategy when considering combined RFA-PEI or either RFA or PEI alone. Combined RFA-PEI significantly improves OS and reduces the risk of local recurrence without increasing major complications. Further large-scale studies are needed to assess economic outcomes and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Radiofrequency ablation (RFA) is a well-known percutaneous approach that has widely been used in the treatment of primary and metastatic hepatic malignancy and lung tumours, with demonstrated effectiveness [6][7][8]. The application of RF ablation in the treatment of extrahepatic cholangiocarcinoma [9], colorectal cancer [10] and oesophagus dysplasia [11] has also been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Radiofrequency ablation (RFA) is a well-known percutaneous approach that has widely been used in the treatment of primary and metastatic hepatic malignancy and lung tumours, with demonstrated effectiveness [6][7][8]. The application of RF ablation in the treatment of extrahepatic cholangiocarcinoma [9], colorectal cancer [10] and oesophagus dysplasia [11] has also been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) continues to be the most prevalent primary malignancy of the liver and is the third leading cause of cancer-related deaths worldwide [1][2][3]. Approximately, 13.5-36.7% patients with HCC will develop extrahepatic metastases (EHM), which are indicative of advanced stage disease according to the Barcelona clinic liver cancer (BCLC) staging system [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…46 Despite the presence of limited randomized trials assessing the value of RFA and PEI compared with RFA, a few metaanalyses have been published. 48,49 In a systematic review including eight trials and 969 patients, Zhu et al reported significantly better OS and complete ablation rates following RFA combined with PEI compared with RFA alone. 49 Finally, two recent retrospective studies investigated the results of RFA and PEI in postsurgical recurrences, compared with hepatic resection.…”
Section: Ablation and Ethanol Injectionmentioning
confidence: 99%